Pengaruh Manfaat dan Kemudahan E-SPT Terhadap Pelaporan E-SPT oleh Wajib Pajak Orang Pribadi (Studi Kasus Pada KPP Malang Selatan) - Mochamad Fatich Aruqot; Afifudin Afifudin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of independent variables on the benefits of e-SPT and the ease of e-SPT and the effect of dependent variables on e-SPT. There were 3 research problems discussed in this study. (1) Did the benefits and convenience of e-SPT affect the reporting of e-SPT by individual taxpayers at KPP South Malang?. (2) Did the benefit of e-SPT affect the reporting of e-SPT by individual taxpayers at KPP South Malang?. (3) Did the ease of e-SPT affect the reporting of e-SPT by individual taxpayers at KPP South Malang?. This research belonged to comparative causal methods used quantitative approach. In this study, researchers tested a hypothesis in the form of a causal relationship between two variables (independent and dependent). The result of this study based on tested using a multiple linear regression model showed: (1) The result of this study simultaneously the Benefits of e-SPT and the Ease of e-SPT had a Significant Positive Effect on the e-SPT Reporting variables at the KPP South Malang. (2) The result of this study was partially the benefits of e-SPT had a significant positive effect on the e-SPT reporting variables in KPP South Malang. (3) The result of this study was partially the ease of e-SPT had a significant positive effect on the e-SPT reporting variable at the KPP South Malang.Keywords : The Effect of Benefits and Convenience, e-SPT, e-SPT Reporting, Taxpayers